Boundary Spanning in Global Organizations. (16th January 2017) - Schotter, Andreas P. J.; Mudambi, Ram; Doz, Yves L.; Gaur, Ajai
Abstract: Global organizations are inherently complex. The spatial dispersion of activities results in organizational subunits becoming embedded in local host‐country contexts that differ from their parents' home country contexts. These subunits are also embedded in their parents' corporate networks, causing them to differ from their locally embedded peers. The dual embeddedness and associated complexities create complex and often implicit boundaries. In addition, the contextual and operational diversity that affects the boundaries in global organizations are continually changing. Hence managing and coordinating across different inter‐ and intra‐organizational boundaries has emerged as an important capability for the success of global organizations. So far, we have a limited understanding of the factors that affect the complexity and effectiveness of the boundary spanning function. In this article, we focus on clarifying these key issues and propose a model for effective boundary spanning in global organizations.